Néo-breton and questions of authenticity - Hornsby, Michael (Sociolinguistic Studies, 2005)
Attempts to revitalize Breton have led to the appearance of a learner variety of the language which is by no means universally accepted. This article reviews the major trends that commentators have taken with regard to this variety –néo-breton– and, as the variety of Breton most likely to survive into the twenty-first century, the likely domains where this variety will be used are examined. Differences with traditional Breton are discussed, as is the controversial nature of néo-breton in the eyes of some commentators and native speakers. Within the field of language death studies, the appearance of ‘neo-’ languages has implications for the stages a language experiencing attrition goes through and whether these ‘neo’ varieties do realistically represent a future for the endangered language. An examination of the differing expectations of various groups involved in the debate seeks to establish common ground between them, through making explicit the different aims of the groups and where these aims converge.